2018
DOI: 10.1038/s41598-018-21313-0
|View full text |Cite
|
Sign up to set email alerts
|

Modified Inguinal Microscope-Assisted Varicocelectomy under Local Anesthesia: A Non-randomised Controlled Study of 3565 Cases

Abstract: Varicocele is a common abnormality, but the conventional microsurgical subinguinal varicocelectomy (CMSV) has some disadvantages. We invented Modified Inguinal Microscope-Assisted Varicocelectomy (MIMV) under local anesthesia. This study aims to evaluate MIMV by comparing it to CMSV in operating duration, time to return to normal activity, postoperative complications, achievement of natural pregnancy and improvement of semen quality for patients with infertility, pain score for those with scrotal pain, and so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…On the contrary, a retrospective study that included 3565 patients with varicocele demonstrated that pain relief in patients treated with inguinal MSV under LA (2% lidocaine) was comparable to the patients treated with subinguinal MSV under GA or SA [ 10 ]. This discrepancy could be attributed to the different anesthetic and surgical regimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, a retrospective study that included 3565 patients with varicocele demonstrated that pain relief in patients treated with inguinal MSV under LA (2% lidocaine) was comparable to the patients treated with subinguinal MSV under GA or SA [ 10 ]. This discrepancy could be attributed to the different anesthetic and surgical regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The preferred anesthesia technique depends on several factors, including the procedure’s suitability for the patient, surgeon choice, patient acceptance, safety, perioperative pain control, the time to return to normal activity, the need for monitoring, and cost-effectiveness. LA is associated with reduced pain, decreased postoperative analgesic requirement, less need for postoperative care, lowered postoperative nausea and vomiting complications, a short anesthesia time and a short hospital stay, compared with GA [ 10 , 11 ]. Although many studies have compared LA and SA or GA for hernia repair, limited studies have compared them for varicocelectomy, and it is not clear whether LA is a suitable alternative to SA or GA for the procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation